2014
DOI: 10.1021/bc500212n
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation and Optimization of Modification Reactions of Oligonucleotides with Amines and Carboxylic Acids for the Synthesis of DNA-Encoded Chemical Libraries

Abstract: DNA-encoded chemical libraries are collections of small molecules, attached to DNA fragments serving as identification barcodes, which can be screened against multiple protein targets, thus facilitating the drug discovery process. The preparation of large DNA-encoded chemical libraries crucially depends on the availability of robust synthetic methods, which enable the efficient conjugation to oligonucleotides of structurally diverse building blocks, sharing a common reactive group. Reactions of DNA derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 39 publications
2
72
0
Order By: Relevance
“…A handful of studies now exist describing the preparation and screening of solution-phase libraries that incorporate diverse reactions—including those rehearsed above—though only with conversion yield data. 2023,3234 We sought to determine whether our assay could be extensible to the investigation of solution-phase DNA-encoded reaction development, and whether and how those data could apply to solution-phase library planning and synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A handful of studies now exist describing the preparation and screening of solution-phase libraries that incorporate diverse reactions—including those rehearsed above—though only with conversion yield data. 2023,3234 We sought to determine whether our assay could be extensible to the investigation of solution-phase DNA-encoded reaction development, and whether and how those data could apply to solution-phase library planning and synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of synthesis conditions on DNA’s informational integrity, and consequently its viability in PCR to generate templates for sequencing-based decoding, is currently not a consideration in the development of new DNA-encoded reactions. 3235 …”
mentioning
confidence: 99%
“…Table 1 Entry 20 provides a method for reacting amines with a bromoacetamide functionalized DNA-conjugate. Franzinin et al 53 have recently reported a similar reaction using chloroacetamide functionalized DNA. Table 1 Entry 21 provides a method for a DNA-conjugated HWE reaction which may be applied to split-and-pool or high-throughput DEL synthesis.…”
Section: Bioconjugate Chemistrymentioning
confidence: 98%
“…19 However, yields for acylation reactions of secondary amines tend to be lower than for primary amine oligonucleotide conjugates. 19 Test biotinylations with two DNA conjugates bearing secondary amines (DNA-DMBG and DNA-AzPro, Scheme 1) provided lower modification yields than for DNA-NH 2 . In a test reaction on pseudosolid phase (200 mM B-NHS, 20 mM DMAP, 2 h, room temperature) biotinylation yields were 33% and 73% for DNA-DMBG and DNA-AzPro, respectively (Supporting Information Figure S3).…”
Section: Acs Combinatorial Sciencementioning
confidence: 99%
“…27 We demonstrate the concept of "cap-and-catch" purification for the attachment of carboxylic acids to amino-modified DNAs, a frequently used reaction for the preparation of DECLs. 19 In this protocol, following the synthesis step, electrophilic biotin reagents cap unmodified amino-DNAs and the resulting biotinylated DNAs can be removed by affinity capture on streptavidin-coated sepharose ( Figure 1). Several tested reaction protocols provided excellent biotinylation yields and enabled the straightforward purification of DNA-conjugates from unreacted amino-DNA.…”
mentioning
confidence: 99%